2018
DOI: 10.1016/j.jdent.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tubule occlusion properties of an experimental stannous fluoride toothpaste: A randomised clinical in situ study

Abstract: Keywords:Crossover Dentine hypersensitivity Dentinal tubule occlusion in situ model Stannous fluoride Toothpaste A B S T R A C TObjectives: To evaluate the ability of a modified in situ model to differentiate dentinal tubule occlusion properties of toothpaste formulations over 10 days of treatment.Methods: This was a single-centre, three-treatment period, crossover, randomised, single-blind study with healthy participants wearing two lower oral appliances, each retaining four dentine samples, for 10 treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Occlusion might occur either at or below the dentine surface ('sub-surface' occlusion) [11]. Stannous fluoride (SnF2) has been shown to occlude dentine tubules [12] and offer resistance to acid challenge [13]. It may offer benefits in reducing erosive dentine wear [14].…”
Section: Introductionmentioning
confidence: 99%
“…Occlusion might occur either at or below the dentine surface ('sub-surface' occlusion) [11]. Stannous fluoride (SnF2) has been shown to occlude dentine tubules [12] and offer resistance to acid challenge [13]. It may offer benefits in reducing erosive dentine wear [14].…”
Section: Introductionmentioning
confidence: 99%
“…Zero et al [ 42 ] showed that all 1400–1450 ppm F dentifrices provide better remineralization than placebo, except for the SnF 2 group. According to West et al [ 43 ] there is a high grade of tubule occlusion in the toothpaste containing 0.454% stannous fluoride and in the fluoride toothpaste containing 0.76% sodium monofluorophosphate brushed dentine samples. There are no statistical differences between the first and second group of study.…”
Section: Resultsmentioning
confidence: 99%
“…Huysmans et al [ 56 ] with their SEM analysis concluded that SnF 2 toothpaste could reduce erosive tooth wear in situ. West et al [ 43 ] concluded that there are no differences in tubule occlusion capability between toothpaste containing 0.454% stannous fluoride and fluoride toothpaste containing 0.76% sodium monofluorophosphate. However, following the acid challenge, there was a statistically significantly greater degree of occlusion in the stannous fluoride toothpaste.…”
Section: Discussionmentioning
confidence: 99%
“…Other in vitro studies with no external oral influences such as oral debris within the model found that imaging the surface did not reveal a complete coating on the surface of the dentine and tubules appeared occluded in the depth of the tubule rather than at the surface [33]. It is therefore important to investigate the tubule occlusion in the depth of the tubule for this agent as opposed to the surface alone in line with the mode of action of a number of other occluding agents, as this will not reveal the potential occlusion benefit for potassium oxalate [34].…”
Section: Discussionmentioning
confidence: 99%